Epidemiological Profile of Fractures Resulting from Bike Accidents - Muhammad Saqib, Slah Ud Din, Tauseef Raza, Ashok Kumar, Saeed Taj Din (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cycling is increasingly promoted as a sustainable and healthy mode of transportation, but it is also associated with a significant risk of traumatic injuries, particularly fractures. Objective: To analyze the demographic patterns, mechanisms of injury, anatomical distribution, treatment modalities, and complications associated with fractures sustained in bike-related accidents. Methods: This retrospective observational study was conducted at Department of health and population THQ level hospital Kot Chutta District Dera Ghazi Khan during November 2021 to March 2023. The study included a total of 280 patients who presented to the emergency or orthopedic departments with confirmed fractures resulting from bike accidents. Patient data were obtained from the hospital’s electronic medical records and trauma registry databases. Results: Out of 280 patients, 198 (70.7%) were male and the mean age was 34.8 years. The most common mechanism of injury was falling from the bicycle (47.1%), followed by vehicle collisions (35%). Upper limb fractures were the most prevalent (53.2%), with distal radius and clavicle being the most commonly affected sites. Surgical treatment was required in 60.4% of cases, and the average hospital stay was 6.3 days. Complications occurred in 13.6% of patients, though no fatalities were recorded. Helmet usage was observed in only 31.8% of the cohort and was associated with a lower incidence of facial fractures. Conclusion: It is concluded that bike-related fractures are common and often serious, particularly among young male cyclists. Upper limb fractures dominate injury profiles, and surgical intervention is frequently necessary. Keywords: Accidents, Patients, Epidemiological, Fractures, Bike